Does Piped Water Reduce Diarrhea for Children in Rural India? - Jalan, Jyotsna; Ravallion, Martin (World Bank, Washington, DC, 2014)
The effects of public investments aimed at directly improving children's health are theoretically ambiguous, since the outcomes also depend on indirect effects through parental inputs. The authors investigate the role of such inputs in influencing the incidence of child health gains from access to piped water in rural India. Using propensity score matching methods, they find that the prevalence and duration of diarrhea among children under five are significantly less on average for families with piped water than for families without it. But health gains largely bypass children in poor families, particularly when the mother is poorly educated. The author's findings point to the importance of combing infrastructure investments with effective public action to promote health knowledge and income poverty reduction.